Comparison of treatment selections by Japanese and US psychiatrists for major depressive disorder: A case vignette study. Issue 9 (17th February 2015) - Nakagawa, Atsuo; Williams, Aya; Sado, Mitsuhiro; Oguchi, Yoshiyo; Mischoulon, David; Smith, Felicia; Mimura, Masaru; Sato, Yuji
<x xml:space="preserve">Abstract</x> Aims A review of the published work on treatments for major depressive disorder suggests that there is an alarming gap between guideline recommendations and actual clinical practices worldwide. The purpose of this study was to compare early‐career psychiatrists' selections of treatment for mild to moderate major depression in Japan and the USA. Methods The authors surveyed 120 early‐career psychiatrists from two residency programs in Japan and the USA using web‐based questionnaires. In response to two case vignettes of mild to moderate major depression, the subjects selected treatment modalities and first‐ and second‐line pharmacotherapy. Results Eighty‐one psychiatrists (68%) returned surveys, of whom 42 (52%) were Japanese and 39 (48%) American. Fewer Japanese subjects selected psychotherapy than Americans. The Japanese psychiatrists favored benzodiazepine monotherapy for the treatment of mild depression, whereas the American psychiatrists favored antidepressant monotherapy. For the initial treatment of moderate depression, approximately half of the Japanese selected antidepressant monotherapy, and a quarter selected benzodiazepine monotherapy, whereas the Americans unanimously selected selective serotonin reuptake inhibitors monotherapy. As a second‐line strategy, the Japanese were more likely to augment medication and less likely to increase dosage for moderate depression than their American counterparts. Conclusions Differences were found between the treatment selections of early‐career psychiatrists in Japan and the USA, despite comparable guidelines and postgraduate training. The results suggest that the gap between guidelines and practice may also be shaped by physician workload, attitudes toward side‐effects, and the sociocultural contexts in which clinical decisions are made.